Failure investigation on deformed superheater tubes - Othman H.; Purbolaksono J.; Ahmad B. (2023)
Investigation is conducted following the discovery of significant deformations and the presence of cracks in the vicinity of welded joints at the superheater tubes of a heat recovery steam generator (HRSG) in a Malaysian Electricity Company's power plant. This study performs the finite element (FE) analyses in order to identify the possible root cause failure of the deformed superheater tubes using software package of MSC PATRAN/NASTRAN. The locations of maximum stress induced by the deformed tube are determined. The correlation between the maximum stress and allowable restriction condition is presented, and it shows good correlations with the findings obtained from the visual inspection on site. 2008 Elsevier Ltd. All rights reserved.